Hierarchically structured bimetallic electrocatalyst synthesized via template-directed fabrication MOF arrays for high-efficiency oxygen evolution reaction. (1st March 2019) - Guo, Meichen; Li, Yao; Zhou, Lingxi; Zheng, Qiaoji; Jie, Wenjing; Xie, Fengyu; Xu, Chenggang; Lin, Dunmin
Abstract: It is of great significance to develop high-efficiency and low-cost electrocatalysts towards oxygen evolution reaction (OER) due to their critical role in the electrochemical water splitting to produce H2 fuel. Herein, a well-controlled hierarchical structured bimetallic electrocatalyst of Co3 O4 @Ni2 P-CoP/NF is constructed via phosphating and carbonating Co3 O4 nanowires template-directed fabrication Ni-substituted ZIF-67 arrays onto a 3D Ni foam substrate. The as-obtained hierarchical structured nanomaterial displays superior electrocatalytic performance with a small overpotential of 298 mV required to achieve the current density of 50 mA cm −2 and reveals high electrocatalytic activity with long-term durability after continuously working for 40 h in 1.0 M KOH. The good performance of the material for OER can be attributed to the synergistic effect of optimized hierarchical structure, partial substitution of Ni for Co, high porosity and N, P-codoping.